Radical ecology in the face of the anthropocene extinction - Smith, John A., 1947 April 16- author.
1 online resource.
Keywords: "This book has two interlocking ambitions. The first is to steer what we purposefully call the idioms of critical philosophy towards a more ecologically-informed paradigm. The second is to recognise that what has rightly come to be called the Anthropocene Extinction is not and cannot be treated as simply a scientific fact but is rather a socio-political and ecological dispute of immense complexity. We start with an exploration of the consequences of a critical tradition which, under the name Enlightenment, has placed humanity at its centre and chance as its most general -and problematic - characteristic. We argue that this leads to a schizophrenic relationship between radical critique and science which can be avoided if we take the implications of biosemiotics seriously and develop a new, ecologically-informed social science. We argue that in practice this means that for science to be practical in addressing to the Anthropocene extinction, we have to recognise that it operates in a historically emergent, highly differentiated techno-political ecology. Science, as it is currently commonly understood and used, is not ecological enough. This book will interest social scientists interested in not only describing and critiquing but also understanding and responding to the complex problems facing humanity; scientists wanting to make sense of social phenomena; those educating the next generation of social scientists; and climate activists and policy makers"--